N-acetil-L-Cisteína e o extrato hidroalcoólico de Psidium guajava exercem efeito protetor frente à toxicidade glutamatérgica em larvas de Danio rerio (peixe-zebra) - Lopes , Andressa Rubim (2019)
Glutamate (Glu) acts as the main excitatory transmitter in the central nervous system of vertebrates. However, in high concentrations, glutamate can cause excessive stimulation of neurons in a process called excitotoxicity. This pathology is involved in numerous neurodegenerative diseases as well as brain injuries. However, clinically available pharmacotherapeutic agents against glutamatergic excitotoxicity are not completely effective, so research on new compounds is necessary. In this study we hope to elucidate the protective effect of N-Acetyl-L-Cysteine (NAC) and the hydroalcoholic extract of Psidium guajava (PG) against excitotoxicity in a model of glutamate exposure effects of Danio rerio (zebrafish) larvae. For this purpose, 3-day post-fertilization (dpf) larvae exposed 10 M Glu were used in 96-well plates for 24 hours (h). After the completion of the treatments, behavioral and cellular viability analyzes were performed. Exposure to glutamate resulted in a significant increase in ROS production, decrease in mitochondrial viability, increase in chromatin damage, and apoptosis. Concomitantly, exposure to glutamate resulted in behavioral changes, such as distance traveled and touch response. On the other hand, NAC treatment demonstrated a protective effect avoiding cell damage and behavioral changes, while PG treatment prevented cell damage. Our data show for the first time a protective effect of NAC and PG against glutamate-induced damage in zebrafish larvae, suggesting that both compounds have therapeutic potential against excitotoxic processes.